Undergraduate Nursing Students' Satisfaction of The Clinical Learning Environment in Iraq-Kurdistan - Zuhair Rushdi Mustafa; Safiya Sabri Piro (Kufa Journal for Nursing Sciences)
Background: Clinical nursing education is a valuable element of any nursing program and leads to better prepare nursing with the required skills to provide safe and high quality care.